Biting Activity and Host Attractancy of Mosquitoes (Diptera: Culicidae) in Manzhouli, China - Wang, Zhong-Ming; Xing, Dan; Wu, Zhi-Ming; Yao, Wen-Jing; Gang, Wang; Xin, Dong-Sheng; Jiang, Yue-Fen; Xue, Rui-De; Dong, Yang-De; Li, Chun-Xiao; Guo, Xiao-Xia; Zhang, Ying-Mei; et al. (Journal of medical entomology, 2012)
The biting activity and host attractancy of vector mosquitoes are important in assessing the risk of arbovirus transmission, especially where migratory and nonmigrating bird species congregate, such as in Hulun Lake, Manzhouli. In 2009, the population distribution, species diversity, biting activity, and host attractancy of mosquitoes were investigated in Hulan Lake and its associated prairie area. The adult mosquitoes were captured either by human volunteers using aspirators in mosquito nets, by CO₂-baited light traps, or by animal-baited traps. In total, 27,004 mosquitoes, representing three genera and 10 species, were collected from Manzhouli, China, in July 2009, of which Aedes dorsalis (Meigen) were most predominant species, followed by Ae. vexans (Meigen). Biting activity peaks by Ae. flavescens (Muller), Ae. dorsalis, and Culex modestus (Facalbi) on human subjects were investigated. Four mosquito species were captured from different animal sheds (sheep, cattle, and goose). Ae. flavescens was more abundant in the cattle shed than in the other two sheds. The Ae. dorsalis in the sheep shed was much higher than in the other animal sheds. The Ae. flavescens collected via chicken-baited traps were significantly higher than those collected via rabbit-baited and pigeon-baited traps. There were no significant differences in the number of Ae. dorsalis and Ae. vexans collected using the three different animal traps.